DISCOURSE MARKERS: THE PLACE AND ROLE IN THE LANGUAGE SYSTEM - Mikhail V. Kamensky (Вестник Северо-Кавказского федерального университета, 2022)
The article contains the results of statistical analysis of the representation of discourse markers, characterized by the prominent cognitive potential, in the language system, as well as their significance in different types of discourse. The research was conducted using the author’s methodology of automated text processing.